Preventing Obesity through Schools. Issue 2 (December 2013) - Nihiser, Allison; Merlo, Caitlin; Lee, Sarah
<x xml:space="preserve">Abstract</x> This paper describes highlights from the Weight of the Nation 2012 Schools Track. Included is a summary of 16 presentations. Presenters shared key actions for obesity prevention through schools. The information provided at the Weight of the Nation can help school health practitioners access tools, apply evidence‐based strategies, and model real‐world examples to successfully start obesity prevention initiatives in their jurisdiction.